Hubungan efikasi diri dengan pengambilan keputusan karier siswa - Sri Mauli; Tanti Ardianti; T. Sunarto (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
this study aims to determine the relationship between self-efficacy and student career decision making. The method used in this study uses quantitative research with the correlation method. The results of hypothesis testing using SPSS 25 with the normality test results show that the significant value is 0.63, the data is normally distributed and the linearity test has a significance value of 0.332 deviation from linearity. The results of the research show that there is a significant linear relationship between the two variables. The results of the product moment correlation analysis show that the results of the correlation test show that H1 is accepted. Because the significance value (2-tailed) of the instrument is 0.000 <0.05, it can be concluded that there is a significant positive relationship between self-efficacy and career decision making in class XII students at SMAN 1 Tegalwaru.